Arbitrary Ruptures: The Making of History in Michael Chabon’s The Yiddish Policemen’s Union (2007) - Otten, Birte (Current Objectives of Postgraduate American Studies, 2012)
Michael Chabon’s alternate history novel The Yiddish Policemen’s Union“ (2007) is one of a few novels of that genre that have received recognition from beyond its fan community. This essay argues that the novel’s success can be attributed to its thematic participation in a post-9/11 public discourse which addresses and complements the generic conventions of alternate history.